Multiple Laser Doppler Flowmetry Probes Increase the Reproducibility of Skin Blood Flow Measurements - Luck, J. Carter; Kunselman, Allen R.; Herr, Michael D.; Blaha, Cheryl A.; Sinoway, Lawrence I.; Cui, Jian (Frontiers in Physiology, 2022)
Cutaneous microcirculatory perfusion is commonly measured using laser Doppler flowmetry (LDF) probes, which provide a continuous, non-invasive quantification of skin blood flow (SkBF). However, inhomogeneities in the skin’s microvasculature density contribute to a decrease in reproducibility whenever an LDF probe is removed and replaced, as is the case during pre- and post-intervention or between-day measurements. Therefore, this study aimed to determine whether increasing the total number of individual LDF probes in a localized area improves the reproducibility of the measurement. Seven laser Doppler probes were secured in a custom-made acrylic holder designed to attach to the skin’s surface easily. SkBF, local skin temperature (Tsk), and blood pressure (BP) were assessed in 11 participants (6 M, 5 F, 42 ± 15 yrs). SkBF and Tsk were measured from the dorsal forearm (arm trial) for five minutes. Next, the multi-laser device was moved to the lateral side of the calf (leg trial), and measurements were obtained for five minutes. Each arm and leg trial was cyclically repeated three times, and all trails were separated by an intermission lasting 10-15 minutes. The average SkBF and the cutaneous vascular conductance (CVC) from all possible LDF probe combinations were not statistically different across the three arm and leg trials. Two-way mixed-effects models with absolute agreement were used to compute the intraclass correlation coefficient (ICC) for CVC, and the minimum ICC increased with the addition of LDF probes. The ICC of the average CVC from seven LDF probes was 0.96 between the arm trials and 0.91 between the leg trials, which suggests that there is excellent reliability and little difference between trials following the removal and replacement of the device. Moreover, all individual ICC values from ≥3 LDF probe combinations were greater than 0.70 (i.e., good reliability). These data suggest that SkBF measurements with multiple laser Doppler probes in a custom-made holder have excellent reproducibility after replacing the probes within the same participant. Therefore, this application could provide more reproducible assessments between repeated measurements (e.g., before and after exercise or clinical procedures) where the LDF probes must be removed and replaced within the same location.